Effects of Tai-Chi and Running Exercises on Cardiorespiratory Fitness and Biomarkers in Sedentary Middle-Aged Males: A 24-Week Supervised Training Study - Yi Wang; Xian Guo; Liangchao Liu; Minhao Xie; Wing-Kai Lam (Biology, 2022)
This study examined the effectiveness of Tai-Chi and running exercises on cardiorespiratory fitness and biomarkers in sedentary middle-aged adults under 24 weeks of supervised training. Methods Thirty-six healthy middle-aged adults (55.6 ± 5.3 yr) were randomly assigned into Tai-Chi, running and control groups. During a 24-week training period, the Tai-Chi and running groups were asked to perform exercises for 60 min/day and 5 days/week, which were supervised by Tai-Chi and running instructors throughout. Resting heart rate, lean mass, blood pressure and blood lipids were measured, and cardiorespiratory fitness (VO2max, Vmax and Peak heart rate) was assessed at the baseline and the 12- and 24-week interventions. Results Compared to the no-exercise control group, both the Tai-Chi and running groups significantly decreased resting heart rate, diastolic blood pressure and cardiorespiratory fitness and increased lean mass across the training session (p < 0.05). Compared to the Tai-Chi group, the running group showed greater improvement in VO2max and Vmax (p < 0.05) and reduced triglyceride and low-density lipoprotein cholesterol (p < 0.05). Conclusion Both Tai-Chi and running exercise showed beneficial effects on cardiorespiratory fitness and enhanced health-related outcomes in middle-aged adults. Although Tai-Chi exercises were less effective in VO2max than running, Tai-Chi may be considered as a plausible alternative to running exercises that can be achieved in the indoor-based setting.